Paper 37: Management of Sublime Tubercle Injuries In Adolescent Throwing Athletes. Issue 7 (30th July 2022) - Fogleman, Sarah; Fronek, Jan; Leek, Bryan; Carroll, Alyssa; Pennock, Andrew; Edmonds, Eric
Objectives: Avulsion fractures of the sublime tubercle of the ulna have been reported as a cause of medial elbow pain and instability in overhead athletes in adolescence and early adulthood. While the management of ulnar collateral ligament (UCL) and medial epicondyle injuries have been extensively described and reported, little has been published on the treatment of the less common bony avulsion fracture of the sublime tubercle. The objective of this study was to characterize injury pattern, treatment, and outcomes for sublime tubercle avulsion fractures in adolescent throwing athletes. Methods: A multicenter retrospective review was conducted from July 2005 to December 2020. Sublime tubercle avulsion fractures were identified by surgeon records or a database query of radiology reports. Inclusion criteria included throwing athletes age ≤19 years old with a sublime tubercle avulsion fracture sustained from a throwing mechanism, identified on at least one radiologic study (radiograph, CT, or MRI). Data collected included demographics, clinical presentation including mechanism of injury, acuity, initial treatment; and outcomes including complications, final range of motion, patient reported symptoms, radiographic union, and return to activities or sport. Results: 14 baseball players were identified with sublime tubercle avulsion fractures with a median age of 16.5 years (range, 15-19). Median duration of follow up was 2.26 years. All athletes were initially managed non-operatively with either rigid immobilization (casting, n=7), or no rigid immobilization (activity modification alone, sling, or removable brace, n=7). Six of the seven athletes treated with casting had favorable outcomes and were able to return to sport; one suffered a reinjury at 10 months and was unable to return to his previous level of play, but declined operative management. Of the seven initially managed without rigid immobilization, two had success and were able to return to sport without additional intervention, one had persistent pain and associated UCL tear but declined surgery; four ultimately proceeded to UCL reconstruction. For the athletes that underwent surgery, two did so for continued pain and associated tearing of the UCL, one for nonunion of displaced sublime tubercle, and one for a reinjury 10 months after full healing of the initial fracture and return to sport. All were able to return to their previous level of throwing postoperatively. Conclusions: As the largest case series of adolescent throwing athletes with sublime tubercle avulsion fractures to date, this study expands our understanding of management of this rare injury. Our results challenge the historical findings that the majority of sublime tubercle avulsion fractures fail non-operative management, and highlight the role for a diligent non-operative protocol with rigid immobilization, which has much better success than removable forms of immobilization or activity modification alone. Unlike purely ligamentous injuries, bony avulsions may be treated nonoperatively with good results and return to high level throwing in adolescent patients. Figure 1. AP radiographs of a simple sublime tubercle fracture on initial presentation (left) and after 3 weeks of immobilization in a long arm cast (right).